Ripensare l’emergenza. Denaturalizzare l’approccio emergenziale nella prima zona rossa italiana durante il Covid-19 - Sparaco, Domenico Maria (Antropologia Pubblica, 2024)
The article analyzes the establishment of Italy’s first red zone during the Covid-19 pandemic, focusing on the Lower Lodi region, and specifically Codogno. It examines the legal frameworks that enabled the implementation of this red zone and delve into immunization protocols, law enforcement, and their socio-political implications. Beyond the official narrative, the article incorporates ethnographic insights, highlighting the lived experiences of those subjected to the red zone’s regulations. The fieldwork reveals the limitations of this governmental intervention, challenging its effectiveness and prompting a reconsideration of emergency management strategies. The study ultimately calls for a critical rethinking of the politics of red zones, advocating for approaches that move beyond the constraints of traditional emergency governance.